2000
DOI: 10.1136/thorax.55.5.364
|View full text |Cite
|
Sign up to set email alerts
|

Generation of complement C3 and expression of cell membrane complement inhibitory proteins by human bronchial epithelium cell line

Abstract: Background-The interrelationship between human airway epithelium and complement proteins may aVect airway defence, airway function, and airway epithelial integrity. A study was undertaken to determine (1) whether unstimulated human bronchial epithelium generates complement proteins and expresses cell membrane complement inhibitory proteins (CIP) and (2) (Thorax 2000;55:364-369)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…The formation of intrapulmonary ICs after allergen exposure may also activate complement cascade (13). According to this hypothesis, activated C5 components are primarily located at the epithelial side of the airway, and, in nonasthmatic individuals, the intrapulmonary activation of complement is well regulated (28). Consistent with this hypothesis, our data demonstrated that intrapulmonary C5 inhibition achieved an efficacy similar to that of systemic C5 inhibition at checkpoint 3 ( Figure 8) and at checkpoint 2 (unpublished observations).…”
Section: Figuresupporting
confidence: 78%
“…The formation of intrapulmonary ICs after allergen exposure may also activate complement cascade (13). According to this hypothesis, activated C5 components are primarily located at the epithelial side of the airway, and, in nonasthmatic individuals, the intrapulmonary activation of complement is well regulated (28). Consistent with this hypothesis, our data demonstrated that intrapulmonary C5 inhibition achieved an efficacy similar to that of systemic C5 inhibition at checkpoint 3 ( Figure 8) and at checkpoint 2 (unpublished observations).…”
Section: Figuresupporting
confidence: 78%
“…These events result in inhibition oxidative burst and bacterial clearance by PMNs due to defective assembly of NADPH oxidase [21]. The ability of lung cells to synthesize C3 and C5 as well as other complement proteins locally can further contribute to the pathogenesis of lung disease [22][23][24].…”
Section: Immune Complex Injury Modelmentioning
confidence: 99%
“…Although C6 production by pulmonary epithelial cells has not been assessed, bronchial epithelial and type II pneumocyte cell lines have been found to produce C3 and C5 (45)(46)(47). Complement synthesis by these cells is upregulated in response to IL-1and TNF-␣.…”
Section: Figurementioning
confidence: 99%
“…Moreover, by 7 days after transplantation, macrophages constituted a large percentage of the infiltrates in the peribronchial, perivascular, and interstitial spaces of lung allografts. In addition, alveolar epithelial cells also produce early components of complement (45)(46)(47). Therefore, we investigated whether lung allografts can be a source of C6.…”
Section: Local C6 Production By Lung Allograftsmentioning
confidence: 99%